2019
DOI: 10.3345/kjp.2018.07255
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obesity and overweight in Iranian children aged less than 5 years: a systematic review and meta-analysis

Abstract: The present study aimed to determine the prevalence of childhood obesity and overweight in Iranian children under 5 years of age using a systematic review and meta-analysis. Methods: We searched MEDLINE (PubMed), Web of Science, Google Scholar, Scopus, CINHAL, and the Iranian databases, including Scientific Information Database (www.sid.ir), Iranian Research Institute for Information Science and Technology (Irandoc.ac.ir), Iranmedex (www.iranmedex.com), and Magiran (www.magiran.com), for all articles published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
3
7
1
Order By: Relevance
“…Sex and regional disparities exist in child malnutrition. In present study, we found that the prevalence of child stunting, wasting, overweight, and obesity were higher among boys than girls in China, which is in accordance with the worldwide nutrition trends based on 2416 population-based measurement studies [24], as well as the studies in European [25,26], American [27], African [28,29], and Asian [30][31][32][33] countries. Consistent with results from other studies [34,35], we found girls have a higher prevalence of underweight in China.…”
Section: Discussionsupporting
confidence: 88%
“…Sex and regional disparities exist in child malnutrition. In present study, we found that the prevalence of child stunting, wasting, overweight, and obesity were higher among boys than girls in China, which is in accordance with the worldwide nutrition trends based on 2416 population-based measurement studies [24], as well as the studies in European [25,26], American [27], African [28,29], and Asian [30][31][32][33] countries. Consistent with results from other studies [34,35], we found girls have a higher prevalence of underweight in China.…”
Section: Discussionsupporting
confidence: 88%
“…Overall about 3 % of Ghanaian children under 5 years were reported overweight in Ghana demography and health survey 2014 (22) which is consistent with the finding of the present study. However, other previous studies reported a higher prevalence of overweight/ obesity among preschool children in developing countries including Ghana as compared to the present study (25) , China (26) , Ethiopia (27) , Lebanon (28) , Iran (29) and Vietnam (30) .…”
Section: Prevalence Of Childhood Overweight/obesitycontrasting
confidence: 91%
“…Regarding overweight’s prevalence, our rate (16.8%) was higher than the regional UNICEF data (7.7%) [ 11 ], Iran (1.23% in 2018) [ 59 ], Jordan (4.7%) [ 35 ], Iraq (9%) [ 11 ], Kuwait (7.1%) [ 11 ], Oman (4.8%) [ 11 ], Saudi Arabia (7.6%) [ 11 ], Palestine (8.5%) [ 11 ], Yemen (2.7%) [ 11 ], Sudan (2.14%) [ 37 ], Algeria (12.9%) [ 11 ], Qatar (13.9%) [ 11 ], and Bahrain (6.4%) [ 11 ], and lower than Egypt (17.8%) [ 11 ], the Syrian Arab Republic (18.2%) [ 11 ], and Tunisia (16.5%) [ 11 ]. Concerning obesity’s prevalence, our findings (8.9%) were higher than Sudan (0.85%) [ 37 ], Jordan (4.7%) [ 35 ], and Iran (8% in 2017) [ 64 ]. In total, the regional average prevalence of overweight and obesity in 2018 (8.69%) [ 60 ] was lower than that reported in our study (12.85%).…”
Section: Discussionmentioning
confidence: 71%